Guidelines for asset integrity management (Wiley, 2017)
This book is an update and expansion of topics covered in Guidelines for Mechanical Integrity Systems (2006). The new book is consistent with Risk-Based Process Safety and Life Cycle approaches and includes details on failure modes and mechanisms. Also, example testing an inspection programs is included for various types of equipment and systems. Guidance and examples are provided for selecting and maintaining critical safety systems. --